Risk-based regulation of higher education in the Philippines a case study - Madrona, Severo C. Jr (Asian Review of Public Administration, 2018)
Risk-based regulations are integrated in public governance as part of public management reform where financial management principles have been introduced within public administration. Of late, risk-based regulations are applied in the regulation of higher educational institution (HEIs) in developed states. Proponents of the framework challenge the one-size-fits-all traditional regulation which applies the same levels of scrutiny to all educational providers, that is, educational providers are subjected to the same process of monitoring and evaluation. It is within this context that this paper is being written. It presents a case study on the application of risk-based regulation of higher education in the Philippines through CHED CMO No.40 Series of 2008 (2008 Manual of Regulation for Private Higher Education) and the CHED CMO No.46 Series of 2012 which introduced the concepts of outcomes-based and typology-based quality assurance of higher educational institutions (HEIs) resultant in their horizontal and vertical classifications. In so doing, this paper examines how CHED (1) defines the risk (2) measures the exposure; (3) sets the strategy to address the exposure and determines how to allocate resources to each individual target by setting the frequency and depth of inspection, and (4) executes and learns the given strategy.